Preparation and Characterization of Bacterial Cellulose and its Composites with Nano Silver Particles of Bioactive Elements - Alaa Abdulnabi Ahmed (Journal of Global Pharma Technology, 2020)
Bacterial cellulose has unique physical and mechanical structural properties. Which qualifies it for use in many industrial, medical and other applications? It is more effective in putting out wounds or burns as it used as a catch to take advantage of one of its advantages, which is its ability to retain fluids for longer due to its low degree of crystallization. Where a study carried out for the preparation of Nano silver cellulose compound of two methods, namely thermal reduction and Electrical mothed. An FT-IR spectrum analysis was s and to know the interconnection between silver Nano particles with bacterial cellulose. The size of the particles was estimated silver nanoparticles of (34.6-35.0) nm respectively for both methods with the AFM technique and to ensure the occurrence of actual adsorption with UV-Vis, SEM and EDX technology, while the x-ray technology showed the shape of silver Nano particles cube and at a volume rate of (4.49, 10.06) nm respectively for both methods and was studied Biological efficacy towards the bacteria of wounds and burns where the results of both methods showed a strong effect to inhibit and stop these bacteria, Finally, compare it to both methods in terms of advantages and disadvantages in terms of the purity of the output was the best but the rate of molecular size and biological effectiveness and time of thermal reduction is the best.Keywords: Bacterial cellulose; Silver nanoparticles; Composites; Antibacterial activity.